Analysis of ice shelf front dynamics in Pine Island Bay (Antarctica) based on long-term SAR time series and deep learning ... - Wagner, Luisa; Baumhoer, Celia; Ullmann, Tobias (Geschäftsstelle der DGPF, 2024)
DGPF-Jahrestagung 2024 - Stadt, Land, Fluss - Daten vernetzen; 33-42 ...